Variación espacio-temporal de fosfatos en la Microcuenca del río Cutuchi utilizando técnicas de estimación geoestadística. - Quispe Rodríguez, Angela Paulina (2018)
The present research evaluated the variation spatio-temporal of the phosphate concentrations in Cutuchi River Microbasin (MRC), which is part of the Pastaza River, the CRM is born in the moors of Cotopaxi volcano thaws, it has an area 2677 km2 and 60 km legth. The rivers contamination phosphates concentration is affected by surface waters eutrophication altering eutrophication. For the investigation, two databases were used, one from the Technical University of Cotopaxi (UTC) and the other one from SEK University, which were monitored since September 2010 to July 2011 by UTC, and by SEK since October to April 2017. Initially, it was realized a data exploratory analysis (AED), to evaluate the distribution and behavior later they were procesed by the package of the Surfer interpolator and finally to realize the spatial distribution maps of phosphates in the MRC. As a result, data was obtained in the AED that has enough outliers, and completed with the mean were interpolated to obtain the three best interpolators: local polynomial, moving averages and polynomial regression for two databases that were valued with the mean square error (EMC). It was concluded that through the best interpolators, phosphate data was obtained in MRC, which were not monitored and to predict its distribution behavior, reducing costs of time and money that the gathering of information in the field would require.